hasilnya
-------------------------------------------------------------------------------------------------------------
#include <stdio.h>
#include <stdlib.h>
int main()
{
float x0,x,x1,x2,x3,fx0,fx1,fx2,f1x,f2x,f3x;
printf("program untuk lagrange interpolasi\n");
printf("masukan nilai x0 : \n");
scanf("%f",&x0);
printf("masukan nilai x1 : \n");
scanf("%f",&x1);
printf("masukan nilai x2 : \n");
scanf("%f",&x2);
printf("masukan nilai x : \n");
scanf("%f",&x);
printf("masukan nilai f(x0) : \n");
scanf("%f",&fx0);
printf("masukan nilai f(x1) : \n");
scanf("%f",&fx1);
printf("masukan nilai f(x2) : \n");
scanf("%f",&fx2);
f1x=(((x-x1)/(x0-x1))*fx0) + (((x-x0)/(x1-x0))*fx1);
f2x=((((x-x1)*(x-x2))/((x0-x1)*(x0-x2)))*fx0) + ((((x-x0)*(x-x2))/((x1-x0)*(x1-x2)))*fx1) + ((((x-x0)*(x-x1))/((x2-x0)*(x2-x1)))*fx2);
// f3x=((((x-x1)*(x-x2)*(x-x3))/((x0-x1)*(x0-x2)*(x0-x3)))*fx0) + ((((x-x0)*(x-x2)*(x-x3))/((x1-x0)*(x1-x2)*(x1-x3)))*fx1) + ((((x-x0)*(x-x1)*(x-x3))/((x2-x0)*(x2-x1)*(x2-x3)))*fx2) + ((((x-x0)*(x-x1)*(x-x2))/((x3-x0)*(x3-x1)*(x3-x2)))*fx3);
printf("hasil====\n");
printf("x0=%f\t| f(x0)=%f\n",x0,fx0);
printf("x1=%f\t| f(x1)=%f\n",x1,fx1);
printf("x2=%f\t| f(x2)=%f\n",x2,fx2);
printf("x =%f\t| f(x) =??\n",x);
printf("f1x=%f\n",f1x);
printf("f2x=%f\n",f2x);
//printf("f3x=%f",f3x);
system("pause");
return 0;
}
hasilnya
No comments:
Post a Comment